Applicability of Lipinski‟s rule of five in drugs used in the treatment of cancer - Surovi, Snigdha Farhana (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.